The correct answer should 1.1333
Answer:
![x = 4](https://tex.z-dn.net/?f=x%20%3D%204)
Step-by-step explanation:
Let's solve:
![2(2−2x)=−3x](https://tex.z-dn.net/?f=2%282%E2%88%922x%29%3D%E2%88%923x)
Step 1: Simplify both sides of the equation.
![2(2−2x)=−3x \\ (2)(2)+(2)(−2x)=−3x(Distribute) \\ 4+−4x=−3x \\ −4x+4=−3x](https://tex.z-dn.net/?f=2%282%E2%88%922x%29%3D%E2%88%923x%20%5C%5C%20%282%29%282%29%2B%282%29%28%E2%88%922x%29%3D%E2%88%923x%28Distribute%29%20%5C%5C%204%2B%E2%88%924x%3D%E2%88%923x%20%5C%5C%20%E2%88%924x%2B4%3D%E2%88%923x)
Step 2: Add 3x to both sides.
![−4x+4+3x=−3x+3x \\ −x+4=0](https://tex.z-dn.net/?f=%E2%88%924x%2B4%2B3x%3D%E2%88%923x%2B3x%20%5C%5C%20%E2%88%92x%2B4%3D0)
Step 3: Subtract 4 from both sides.
![−x+4−4=0−4 \\ −x=−4](https://tex.z-dn.net/?f=%E2%88%92x%2B4%E2%88%924%3D0%E2%88%924%20%5C%5C%20%E2%88%92x%3D%E2%88%924)
Step 4: Divide both sides by -1.
![\frac{ - x}{ - 1} = \frac{ - 4}{ - 1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%20x%7D%7B%20-%201%7D%20%20%3D%20%20%5Cfrac%7B%20-%204%7D%7B%20-%201%7D%20)
Therefore, the answer will be x = 4.
Answer:
The square of a monomial is ![(9x^2)^2](https://tex.z-dn.net/?f=%289x%5E2%29%5E2)
Step-by-step explanation:
Consider the provided monomial.
![81x^4](https://tex.z-dn.net/?f=81x%5E4)
We need to Write the expression as a square of a monomial.
The above expression can be written as:
![9\times 9\times x^2\times x^2](https://tex.z-dn.net/?f=9%5Ctimes%209%5Ctimes%20x%5E2%5Ctimes%20x%5E2)
![9^2(x^2)^2](https://tex.z-dn.net/?f=9%5E2%28x%5E2%29%5E2)
![(9x^2)^2](https://tex.z-dn.net/?f=%289x%5E2%29%5E2)
Hence, the square of a monomial is ![(9x^2)^2](https://tex.z-dn.net/?f=%289x%5E2%29%5E2)
Answer is in the pic above. Theorems used:
Exterior angle theorem
Inscribed angle theorem.
![\angle EBF=32.5°](https://tex.z-dn.net/?f=%20%5Cangle%20EBF%3D32.5%C2%B0)